A ordem da participação: Eric Voegelin e a ontologia do ser finito - Cleto, Marcelo de Souza (2015)
The theory of participation developed by the dialectical science assumes the ontological meaning of the intermediate conceptually called by the ancient tradition of metaxy philosophy. In contemporary times the debate on the concept of property got an epistemological relief according to the reflections made by the philosopher and political scientist Eric Voegelin. The author s interpretation of the work scaled its ontology prioritized by the political substance of the human, which finds in the intermediate causal nexus of its participation in the other dimensions of the being (daimon, cosmos and society). After examining the mutual participation within the community of the being the thesis presents the problems of the modernity of metaxy, which highlighted in contrast with the gnosis, puts the term via historiogenesis the tension between truths. The victory of a representation of the truth culminated in a history of order, explained since the representative experiences of archaic Greek tradition as myths (Hesiod) and rites (Dionysus). The route of the investigation enhances the history, the criticism of positivism and the differences brought to light through the development of archeology, a fact that made possible the specific treatment of experiences that are retroactive to the noetic period. The hypothesis of ontological plethora of finite being is confirmed following the logic of the identical and different, unfolded into its continuities and discontinuities ranging from the evocative and transcendent character of symbols to the present intentionality in the philosophies of Anaximander and Heraclitus